2016
DOI: 10.21767/2321-547x.1000004
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cell Extracts from Skin, Placenta, Mesenchyme with Collagen and Elastin in Aesthetic Dermatology and Skin Revitalization: Evaluation of Outcomes in Cohort Study

Abstract: Aging-related changes of the skin are characterized by reduction of the elasticity, moistness and thickness, appearance of wrinkles, pigmented spots, lentigos, and keratosis. Histological changes include thinning of epidermis, flattening of epidermal-dermal interface, reduction of production and disorganization of collagen and elastin, slowdown of cell turnover, reduction of melanocytes and their erratic activity and the phenomenon of solar elastosis.The objectives of the study were to evaluate the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Mesotherapy is another area of cosmetics where elastin may be an excellent candidate for enhancing skin restoration and achieving healthy, young-looking skin. Klokol et al (2016) analysed the performance of a cocktail containing cell extracts from the placenta, skin and mesenchyme with collagen and elastin on 26 women aged 40-65. They concluded that the cocktail had an overall effect as an anti-ageing product because it promoted biosynthesis of new collagen and elastin fibres, reduced senile lentigos and non-uniform pigmentation and decreased skin roughness [52].…”
Section: New Applicationsmentioning
confidence: 99%
“…Mesotherapy is another area of cosmetics where elastin may be an excellent candidate for enhancing skin restoration and achieving healthy, young-looking skin. Klokol et al (2016) analysed the performance of a cocktail containing cell extracts from the placenta, skin and mesenchyme with collagen and elastin on 26 women aged 40-65. They concluded that the cocktail had an overall effect as an anti-ageing product because it promoted biosynthesis of new collagen and elastin fibres, reduced senile lentigos and non-uniform pigmentation and decreased skin roughness [52].…”
Section: New Applicationsmentioning
confidence: 99%
“…Stem cells also possess the capacity to generate peptides that hold potential for therapeutic applications in the treatment of various diseases. For example, the clinical outcomes of organ-specific mammalian precursor stem cell-derived peptide preparations [6][7][8], manufactured by European Wellness laboratories, have been documented in both historical and scientific journals [9][10][11] across a wide range of diseases and illnesses where treatment options are limited.…”
Section: Introductionmentioning
confidence: 99%